Resilient entrepreneurs? — revisiting the relationship between the Big Five and self-employment - Petrik Runst; Jörg Thomä (Small Business Economics, 2022)
The Big Five personality traits and their influence on entrepreneurial action have been repeatedly studied using a trait-based approach. The present paper partly deviates from this perspective by analysing the role of personality prototypes in relation to entrepreneurship. This person-centred approach suggests that combinations of Big Five traits form individual personalities. By using data from the German Socio-Economic Panel (SOEP), we show that at least three prototypes can be identified, one of which — the resilient type — can be hypothesized to significantly increase the likelihood of entrepreneurial action. Our regression results provide evidence of a positive impact of this prototype on the likelihood of and transitioning into self-employment but not the likelihood of exit. We also show that the prototyping approach explains individual self-employment decisions over and above what can already be explained by the profiling approach, another person-centred Big Five approach. The paper concludes with implications for policy and research.
Keywords: D91; L26; M13; 330; Entrepreneurship; Self-employment; Big Five; Personality; Prototypes; Profiles